2009
DOI: 10.1007/s10616-009-9193-0
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic effects of nine Helichrysum taxa in human lymphocytes culture

Abstract: Helichrysum Mill. (Asteraceae) species have been used in folk medicine for thousands of years in the world. The in vitro cytogenetic effects in human lymphocytes of nine Helichrysum taxa used in Turkey folk medicine were investigated. Blood samples were obtained from healthy donors, nonsmoking volunteers, which were incubated and exposed to increasing concentrations of methanol extracts of Helichrysum taxa (0.01, 0.05, 0

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 38 publications
0
30
0
2
Order By: Relevance
“…Considering cultures with co-treatment, our results revealed that the extracts of T. chamaedrys at concentrations of 500 and 1,000 lg/ml and T. montanum at all tested concentrations (125-1,000 lg/ml) significantly decreased the NDI compared to the MMC-treated cells alone; this decrease in cell proliferation may be explained by permitting the repair of MMC induced DNA damages. Eroglu et al (2009) considered that by permitting repair of genotoxic lesions, mitotic delay may have changed the frequency of cells with two or more nuclei at the time of harvest by changing the number of cells that underwent mitosis.…”
Section: Discussionmentioning
confidence: 99%
“…Considering cultures with co-treatment, our results revealed that the extracts of T. chamaedrys at concentrations of 500 and 1,000 lg/ml and T. montanum at all tested concentrations (125-1,000 lg/ml) significantly decreased the NDI compared to the MMC-treated cells alone; this decrease in cell proliferation may be explained by permitting the repair of MMC induced DNA damages. Eroglu et al (2009) considered that by permitting repair of genotoxic lesions, mitotic delay may have changed the frequency of cells with two or more nuclei at the time of harvest by changing the number of cells that underwent mitosis.…”
Section: Discussionmentioning
confidence: 99%
“…H. arenarium, an infusion of the bright yellow flowers, is used in the treatment of gallbladder disorders and as a diuretic in treating rheumatism and cystitis. It is a component in zahraa, an herbal tea used for medicinal purposes in some countries [20]. A. sativum and T. parthenium have a broad spectrum of biological activity.…”
Section: Introductionmentioning
confidence: 99%
“…This fixation step was repeated three times. Slides were air-dried and stained with giemsa (Eroglu et al 2009). …”
Section: Chemicalsmentioning
confidence: 99%
“…The MN staining was performed according to Eroglu et al (2009). The slides were scored by a single observer.…”
Section: Staining and Examination Of Micronucleusmentioning
confidence: 99%